Recent advances in genetics of aggressive behavior - J. D. Davydova; S. S. Litvinov; R. F. Enikeeva; S. B. Malykh; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции)
One of the most important problems of modern neurobiology and medicine is an understanding of the mechanisms of normal and pathological behavior of a person. Aggressive behavior is an integral part of the human psyche. However, environmental risk factors, mental illness and somatic diseases can lead to increased aggression to be the biological basis of antisocial behavior in a human society. An important role in development of aggressive behavior belongs to the hereditary factors that may be linked to abnormal functioning of neurotransmitter systems in the brain yet the underlying genetic mechanisms remain unclear, which is due to a large number of single nucleotide polymorphisms, insertions and deletions in the structure of genes that encode the components of the neurotransmitter systems. The most studied candidate genes for aggressive behavior are serotonergic (TPH1, TPH2, HTR2A, SLC6A4) and dopaminergic (DRD4, SLC6A3) system genes, as well as the serotonin or catecholamine metabolizing enzyme genes (COMT, MAOA). In addition, there is evidence that the hypothalamic-pituitary system genes (OXT, OXTR, AVPR1A, AVPR1B), the sex hormone receptors genes (ER1, AR), neurotrophin (BDNF) and neuronal apoptosis genes (CASP3, BAX) may also be involved in development of aggressive behavior. The results of Genome-Wide Association Studies (GWAS) have demonstrated that FYN, LRRTM4, NTM, CDH13, DYRK1A and other genes are involved in regulation of aggressive behavior. These and other evidence suggest that genetic predisposition to aggressive behavior may be a very complex process.